Investigation of Photocatalytic Degradation of Rhodamine B by Using NanoSized TiO2 (International Journal of Scientific Research and Management (IJSRM), 2017)
In present work investigation of photocatalytic degradation of Rhodamine B dye has been done using nanosized TiO2. In photocatalytic degradation the decomposition of rhodamine-B dye has been done using UV illumination using TiO2 Nanoparticles. In present work the absorbance of the reaction mixture has been measured at various time intervals using Spectrophotometer. Control experiments confirm the necessity of light, semiconductor catalyst and oxygen to follow the photocatalytic path to proceed the photobleaching of dye. Effect of pH, amount of photocatalyst [TiO2], initial dye concentration has been studied over photocatalytic degradation of Rhodamine B. A tentative mechanism has also been proposed